Estimation of A Posteriori Computational Error by the Higher Order Multipoint Meshless FDM - Jaworska, Irena; Orkisz, Janusz (COMPUTING AND INFORMATICS, 2018)
The main objective of this paper is to present a possibility of high quality a posteriori error evaluation based on reference solutions obtained by means of the new multipoint meshless finite difference method. Due to its higher order approximation, the multipoint results may be used as improved reference solution instead of the true analytical one to estimate the errors. Several types of a posteriori error estimators which can be used to evaluate the calculation error are described here. The results of selected numerical benchmarks are considered.